“What happens when you get corona?”: Children’s questions and parental responses about the COVID-19 pandemic - Graciela Trujillo Hernández; David Menendez; Seung Heon Yoo; Rebecca E. Klapper; Maria H. Schapfel; Kailee A. Sowers; Victoria E. Welch; Karl S. Rosengren (PLoS ONE, 2025)
Information discussed between parents and children provide a foundation for children's developing understanding of health and illness. Parents of 3-to-7-year-old children (N = 516, 62% female, 78% White) residing in the United States were recruited using Amazon’s Mechanical Turk during July 29th– August 10th, 2020. We asked parents to report three questions that their children had asked about the COVID-19 pandemic and asked them to report how they responded to those questions. Children’s questions focused on lifestyle changes (22%), while parental responses were often about the virus (23%). We examined the stability of content of children’s questions and parental responses between the first peak and second peak of infection and death rates due to COVID-19 in the United States. The topic of children’s questions and the types of parental responses shifted between the two peaks, such that parents during the second peak of the pandemic reported their children asking more frequently about the virus and preventive measures than children in the first peak. Meanwhile, parents during the second peak of infection and death rates were more focused on responding to their children’s questions with information about the virus. We used Latent Class Analysis to explore overall patterns in children’s questions and parents’ responses. For children’s questions, three latent classes were obtained: (1) the virus [39%], (2) the virus/lifestyle changes [21%], and (3) lifestyle changes/preventive measures [40%]. For parents’ responses three latent classes were found: (1) the virus/self-protection [54%], (2) reassurance/the virus [28%], and (3) simple yes/no answers without further explanation [17%]. These results suggest that children’s questions and parental responses can be captured in terms of a discrete number of latent classes.